Effects of Whole Body Electrostimulation Associated With Body Weight Training on Functional Capacity and Body Composition in Inactive Older People - Evangelista, Alexandre Lopes; Alonso, Angelica Castilho; Ritti-Dias, Raphael M.; Barros, Bruna Massaroto; Souza, Cleison Rodrigues de; Braz, Tiago Volpi; Bocalini, Danilo Sales; Greve, Julia Maria D'andréa (Frontiers in Physiology, 2021)
Objective: To analyze the effects of whole body electrostimulation (WB-EMS) with body weight training on functional fitness and body composition of older men. Methods: Twenty physically inactive older men were randomized into: Control group (control), performed the body weight exercise training wearing electrostimulation clothing, but without receiving electrical current stimuli, (n = 10), and body weight associated with whole body electrostimulation group (BW+WB-EMS), performed the body weight exercise training wearing electrostimulation clothing plus whole body electrostimulation, (n= 10). The training sessions were performed twice a week for six weeks and included eight exercises using body weight, performed in two sets of 8 repetitions. Physical function was assessed using a battery composed of seven tests, six derived from the Senior fitness test and a handgrip strength test. We also measured the muscle thickness of the biceps and triceps brachii and vastus lateralis. Results: The BW+WB-EMS group presented increased (p<0.05) performance in the 30-sec chair stand test (10.2±3.3 vs. 13.8±5.0; reps), arm curl (16.6±3.9 vs. 19.9±6.1; reps), 6-minute walk test (402±96 vs. 500±104; m), and handgrip strength test (30±11 vs. 32 ± 11;kgf). The BW+WB-EMS group also presented increased muscle thickness (p<0.05) in the biceps brachii (17.7 ± 3.0 vs. 21.4±3.4; mm), triceps brachial (14.7±3.6 vs. 17.5±4.1; mm), and vastus lateralis muscles (15.1±2.6 vs. 18.6±4.3; mm). Moderate correlations were found in arm curl (p=0.011; r= 0.552) but not handgrip strength (p=0.053; r= 0.439) with changes in the biceps MT. Moderate changes in the 6-minute walk distance were significantly correlated with changes in vastus lateralis MT (p=0.036; r= 0.471). There was a moderate correlation between the changes in the 30-sec chair stand test (p=0.006; r= 0.589) and changes in the vastus lateralis MT. Furthermore, although a moderate correlation (r= 0.438) was found between triceps MT and handgrip strength no significant difference (p=0.053) was reported. Additionally, there were no statistical differences in any parameters for the control group. Conclusion: WB-EMS with body weight training increased functional fitness, muscle thickness, and lean mass, and decreased body fat in physically inactive older men.